1994
DOI: 10.1093/carcin/15.8.1703
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation pathway for the formation of DNA adducts of the carcinogen 2-amino-l-methyl-6-phenyUmidazo[4,5-b]pyridine (PhIP) in rat extrahepatic tissues

Abstract: The food-borne mutagen 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) induces tumors in colon of male rats and has been implicated in the etiology of human cancers, particularly colorectal cancer. This study was conducted to examine: (1) the biliary and/or circulatory transport of N-hydroxy-PhIP and its N-glucuronides, N-sulfonyloxy-PhIP and N-acetoxy-PhIP; (2) their role as proximate and ultimate carcinogenic metabolites of PhIP; (3) the potential role of glutathione in modulating PhIP-DNA adduct form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 0 publications
6
95
0
Order By: Relevance
“…These carcinogens are indirect-acting so that in order to elicit their carcinogenicity they must first be metabolically converted to DNA-binding species, and this process is largely catalysed by cytochromes P450 [27]. Such bioactivation can take place in situ, but there is also experimental evidence to support the view that reactive intermediates generated in the liver, the principal site of bioactivation, may be transported to extrahepatic tissues although the underlying mechanism(s) remain elusive [28,29]. A number of studies have linked pulmonary CYP1 activity to human cancer incidence, denoting the importance of in situ metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These carcinogens are indirect-acting so that in order to elicit their carcinogenicity they must first be metabolically converted to DNA-binding species, and this process is largely catalysed by cytochromes P450 [27]. Such bioactivation can take place in situ, but there is also experimental evidence to support the view that reactive intermediates generated in the liver, the principal site of bioactivation, may be transported to extrahepatic tissues although the underlying mechanism(s) remain elusive [28,29]. A number of studies have linked pulmonary CYP1 activity to human cancer incidence, denoting the importance of in situ metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are further supported by rodent studies that have shown DiMeIQx (48) and PhIP (49-51) to enhance pancreatic carcinogenesis. PhIP DNA adducts are formed at high levels in the pancreas of animals (52,53) and have been detected with higher intensity in pancreatic tissue of cancer patients compared with noncancer controls (54,55). Polymorphisms in genes that are involved in HCA metabolism have also been associated with pancreatic cancer (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, caffeine treatment was found to significantly increase the incidence of colon adenomas. Other investigators have demonstrated that caffeine can enhance PhIP induction of colonic aberrant crypt foci [Tsuda et al, 1999], possibly by influencing levels of CYP1A2 or N-acetyltransferase in colonic tissue, or biliary transport of conjugated N-hydroxy-PhIP, which is then deconjugated by the intes- tinal flora [Kaderlik et al, 1994]. Epidemiological studies investigating a possible relationship between caffeine consumption and breast [Boyle et al, 1984;Phelps and Phelps, 1988] and colon [Slattery et al, 1990[Slattery et al, , 1999 cancers in humans have yielded inconstant and inconclusive results.…”
Section: Discussionmentioning
confidence: 99%